Implementation of E-learning in Satya Wacana Christian Senior High School (Journal of Economic Education, 2022)
E-learning is a form of technology implementation that is intended to assist the learning process which is packaged in digital electronic form in hopes that learning objectives are achieved. This research was conducted to find out the implementation of e-learning through lesson plan, learning implementation and evaluation. In addition, this study analyzes the level of perception of the use of e-learning through the analysis of technology acceptance models and objectives as well as analyzes the constraints of e-learning implementation. This type of research is a mixed method research. The population of this research is the Satya Wacana Christian high school teachers. Sampling using a saturated sample technique. Data collection techniques using documentation techniques, interviews and questionnaires. The analysis method uses Miles and Huberman model analysis and percentage descriptive. The results of the study show that the implementation of e-learning in Christian Satya Wacana senior high schools includes three stages, namely learning planning, learning implementation, and learning evaluation. The perception of e-learning learning in Satya Wacana Christian senior high school is very useful with the category of “strongly agree” and the implementation of e-learning in Satya Wacana Christian senior high school very easy to use is within the category of “strongly agree” so the purpose of e-learning in Satya Discourse Christian high school has achieved the desired goal. There are several hindrances to e-learning in Satya Wacana Christian senior high school, namely internal and external.